Justice, fuel poverty and disabled people in England. (November 2015) - Snell, Carolyn; Bevan, Mark; Thomson, Harriet
Abstract: This paper considers the relationship between fuel poverty, disabled people, and policy changes in England, drawing on concepts of justice to deconstruct and explain empirical findings. Drawing on statistical analyses of the English Housing Survey, the paper presents three key findings. Firstly that fuel poverty rates in England are typically higher amongst households containing disabled people; secondly that high levels of fuel poverty are found amongst single disabled people of working age; and thirdly, that a greater proportion of households containing disabled people are on prepayment meters compared to other households. These distributional inequalities are explored in terms of 'justice as recognition'. The paper concludes that the distributive inequalities evident in the findings may have been driven by a lack of recognition by energy policy makers in terms of their understanding of the highly varied needs of disabled people, the impact of current measures of fuel poverty, and the way in which disability benefits are understood within calculations of fuel poverty. Moreover, it is argued that current political rhetoric that typically marginalises disabled people of working age on low incomes has further driven distributional inequalities.